Left atrial strain evaluation and prognostic value in constrictive pericarditis patients undergoing pericardiectomy. (14th October 2021) - Lo Presti, S; Chan, N; Saijo, Y; Wang, T; Klein, A
Abstract: Background: Left Atrial (LA) phasic volumes analyses is flawed with geometrical assumption requiring high endocardial border definition. LA strain analysis is an emergent technique that overcome some of these technical limitations. Prior studies of LA mechanics in pericardiectomy patients found improvement in LA strain at follow-up and manifested as symptomatic improvement, however their relationships with survival have not been investigated. Purpose: We assessed LA strain before and after pericardiectomy and its association with all- cause mortality. Methods: Consecutive patients with constrictive pericarditis who underwent pericardiectomy from 2000–2017 were retrospectively analyzed, analyzing pre-operative and post-operative (at 12 months) echocardiography. Exclusion criteria included atrial fibrillation, previous left sided valve surgery, concomitant valvular surgery at the index pericardiectomy, more than mild left sided valvulopathy and poor echocardiographic windows. Strain analyses was performed with Vector velocity imaging independent software. Univariate and multivariable analyses were utilized to identify factors associated with reduced survival. Results: Amongst 190 patients included in the analyses, mean age was 58.5±12.7 years and 37 (19.5%) were female. The etiology of constriction was deemed idiopathic in 61.6% of the cases, median time interval surgery-postoperative echo was 67 days (IQR 6, 312 days). During median follow up of 3.3 years (IQR 0.73, 5.9 years) there were 37 deaths. After surgery, there was a significant decrease in LA reservoir, conduit and regional wall strains. (Table 1). Multivariable analysis demonstrated that postoperative 4C AL strain reservoir was independently associated with all-cause mortality (Table 2). Conclusions: In pericardiectomy patients, postoperative 4C LA strain reservoir is independently associated with all-cause mortality. Perhaps, compensatory changes of septal and antero-posterior walls during constriction explain why after surgery these walls become less dynamic, negatively impacting the overall function. Overall, LA quantification and strains may become a useful clinical tool for risk stratification in pericardiectomy patients Funding Acknowledgement: Type of funding sources: None.